The Study on Customer Characteristics in Mobile Banking Application (MB App) Usage Behaviour with Moderating Effects of Awareness and Experience of Customers in Sri Lanka - MarTech Vs FinTech - Dilogini, S. (University of Jaffna, 2020)
The Covid-19 has exaggerated customers‟ MarTech (Marketing Technology) usage behaviour. In line with FinTech (Financial Technology) in banking, digital application marketplace, e.g., MB apps (Mobile Banking Applications), usage intention has been recognized as a current MarTech usage behaviour in the marketing automation platforms. However, the reviews of past studies indicate that there is no distinct framework for customers’ usage behaviour in the MarTech domain. This study enhances knowledge on the MarTech domain in FinTech organizations by proposing a new conceptual model. The conceptual model presented expands the number of potential research areas by triangulating three theories. Researchers collected responses from 400 MB app customers from Sri Lanka (SL) using a longitudinal survey, and the hypotheses were tested via PLS-SEM by applying Smart-PLS software. The proposed integrated MarTech usage behaviour model (IMTUBM) and integrated MB app usage behaviour model (IMBUBM) provide a basis for understanding customer characteristics in the MarTech domain. Meanwhile, the study conceptually illustrated awareness while logically explaining that experiential aspects are formed by two concepts (previous experience and pre-experience). However, the current pre-experience with MarTech has been proposed as a new moderator in this study that can be better explored than the concept of previous experience. The findings of this study open up new avenues for future research in this emerging MarTech domain. In terms of managerial contributions, this study persuades MarTech marketers to pay greater attention to customer characteristics and create better strategies based on MarTech awareness. Magnificently, it also makes managers engage/think more with/on current pre-experience deliveries related to MarTech to reduce the gap between customers’ MarTech usage intention and behaviour.
Keywords: Awareness; FinTech organization; MarTech domain; MB app; Pre-experience; Sri Lanka